Perancangan Mebel Multifungsi untuk Apartemen Mahasiswa Desain - Teddy Pintono; Lintu Tulistyantoro; Filipus Priyo Suprobo (Intra, 2018)
Apartment is one of the favorite residential facilities for students. The problem is, the apartments have limited space and can not accommodate their activities, especially design students with their tasks. The complexity of student activities should be accommodated in the rooms that are their private spaces. Therefore, multi-functional furniture design with space-saving and flexible properties is needed to solve user problems. This design begins by conducting surveys and collecting literature data on apartments, multi-function furniture, and design student activities as users. Based on the data, it is necessary the concept of multifunctional furniture that can meet the needs of design students in the apartment to the fullest. The concept, named "Maximini", is aimed at making this multifunctional furniture a means for complex design student activities that can be accommodated by a single multi-function furniture even with limited space. The final design was in the form of shelf and table that use the folding system which is very effective for narrow living spaces.